Beastly bones - Ritter, William, 1984- (Ritter, William, 1984- Jackaby series, 2015)
In 1892, New Fiddleham, New England, things are never quite what they seem, especially when Abigail Rook and her eccentric employer R.F. Jackaby are called upon to investigate the supernatural. First, a vicious species of shape-shifters disguise themselves as a litter of kittens, and a day later, their owner is found murdered with a single mysterious puncture wound. Then in nearby Gad's Valley, now home to the exiled New Fiddleham police detective Charlie Cane, dinosaur bones from a recent dig mysteriously go missing, and an unidentifiable beast starts attacking animals and people, leaving their mangled bodies behind. Charlie calls on Abigail for help, and soon Abigail and Jackaby are on the hunt for a thief, a monster, and a murderer.